2017
DOI: 10.1016/j.tiv.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Skin contamination as pathway for nicotine intoxication in vapers

Abstract: Growing warnings on health effects related to electronic cigarettes have met inconclusive findings at present. This study analyzed the in vitro percutaneous absorption of nicotine resulting by skin contamination with two e-liquids (refill 1 and 2) containing nicotine at 1.8%. Donor chambers of 6 Franz cells for each refill liquid were filled with 1mL of nicotine e-liquid for 24h; at selected intervals, 1.5mL of the receptor solutions were collected for nicotine concentration analysis by mean gas chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Nicotine was the dominant chemical in our field site ECEAR samples. This is of concern because nicotine is water and lipid soluble, and readily permeates into skin (Maina et al, 2017;, where it can accumulate and be released into the blood after exposure (Bekö et al, 2017). Nicotine can cause dermatitis, irritation, and skin sensitization in humans (Berlin et al, 2014;Berner et al, 1990;Bircher et al, 1991;Gourlay et al, 1999;Greenland et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine was the dominant chemical in our field site ECEAR samples. This is of concern because nicotine is water and lipid soluble, and readily permeates into skin (Maina et al, 2017;, where it can accumulate and be released into the blood after exposure (Bekö et al, 2017). Nicotine can cause dermatitis, irritation, and skin sensitization in humans (Berlin et al, 2014;Berner et al, 1990;Bircher et al, 1991;Gourlay et al, 1999;Greenland et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…EC users often come into contact with nicotine when handling products, when fluids spill, or when touching surfaces contaminated with EC fluids or residue [20][21][22][23]. In vitro studies have demonstrated transmembrane absorbance of nicotine from e-liquids [24], although its effects have not been characterized. Nicotine exposure from e-liquid spills have been reported in vape shops [20], and significant amounts of nicotine (4.571 g of nicotine/168.75 cm 2 fabric) accumulated in a vape shop during a month of monitoring [23].…”
Section: Introductionmentioning
confidence: 99%